Comparative Analysis and Study of an Automobile Transmission Shell and Finished Product by Modal Test - Wu Wenxuan; Ma Weijin; Zhang Jipin; Wang Junyuan (Jixie chuandong)
Taking the type of automobile transmission shell as a research object,in order to analyze and judge the performance of an automobile transmission shell,the experimental modal analysis of the automobile transmission shell and finished product is carried out by using the experimental modal analysis technique,comparison the results of extracted the parameter of automobile transmission shell and finished product,the results show that,the automobile transmission shell and the finished product corresponding to each other under 1500 Hz,the modal frequency has a small change in a certain frequency band,the modal damping ratio of the finished product is higher than the auto transmission shell,this provides a revised proposal and an important technical support for the following research of automobile transmission shell.